Does verbatim sentence recall underestimate the language competence of near-native speakers? - Schweppe, Judith; Barth, Sandra; Ketzer-Nöltge, Almut; Rummer, Ralf (Frontiers in Psychology, 2015)
Verbatim sentence recall is widely used to test the language competence of native and non-native speakers since it involves comprehension and production of connected speech. However, we assume that, to maintain surface information, sentence recall relies particularly on attentional resources, which differentially affects native and non-native speakers. Since even in near-natives language processing is less automatized than in native speakers, processing a sentence in a foreign language plus retaining its surface may result in a cognitive overload. We contrasted sentence recall performance of German native speakers with that of highly proficient non-natives. Non-natives recalled the sentences significantly poorer than the natives, but performed equally well on a cloze test. This implies that sentence recall underestimates the language competence of good non-native speakers in mixed groups with native speakers. The findings also suggest that theories of sentence recall need to consider both its linguistic and its attentional aspects.